Flash forward : an illustrated guide to possible (and not so possible) tomorrows - Eveleth, Rose, 1987-; Lubchansky, Matt; Goldstein, Sophie (Abrams ComicArts, 2021)
"In this innovative collection of comics and essays, Rose Eveleth poses provocative questions about our future, which are brought to life in twelve brand-new comics, each by a different acclaimed artist. Eveleth then reports on what is complete fantasy and what is only just out of reach. Introducing compelling visions of our potential to progress or wreak destruction, [this book] reveals how complicated, incredible, frightening, and curious our future might be."--Back cover.